Implementasi Fungsi Manajerial Kepala Sekolah dalam Penyelenggaraan Penjaminan Mutu Sekolah di SMA Negeri 10 Palembang - Sri Mastuti (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aims to describe and analyze the implementation of managerial functions of headmaster and obstructing factors in applying the school quality assurance in SMA Negeri 10 Palembang. The method of the study was descriptive method with qualitative approach. The data were got by observing, interviewing, and analyzing the documents. The informen of this study were a headmaster, vice headmasters, the school quality assurance team, and some respondents to strengthen the data. The data were analyzed by reducing, displaying, and concluding data. The results showed that the headmaster managed the program by managing the management functions, those were planning, organizing, actuating, and controlling. The obstructing factors of applying the school quality assurance were in Standar Pendidik dan Kependidikan and Standar Sarana dan Prasarana. Key words: Managerial functions; school quality assurance This study aims to describe and analyze the implementation of managerial functions of headmaster and obstructing factors in applying the school quality assurance in SMA Negeri 10 Palembang. The method of the study was descriptive method with qualitative approach. The data were got by observing, interviewing, and analyzing the documents. The informen of this study were a headmaster, vice headmasters, the school quality assurance team, and some respondents to strengthen the data. The data were analyzed by reducing, displaying, and concluding data. The results showed that the headmaster managed the program by managing the management functions, those were planning, organizing, actuating, and controlling. The obstructing factors of applying the school quality assurance were in Standar Pendidik dan Kependidikan and Standar Sarana dan Prasarana. Keywords: Managerial functions; school quality assurance